2008
DOI: 10.1007/s00542-007-0552-5
|View full text |Cite
|
Sign up to set email alerts
|

Resin micromachining by roller hot embossing

Abstract: The roller hot embossing is an efficient process of manufacture in which patterns are continuously transcribed on film, etc. Recently, the application of the embossing roll to the manufacturing processes of micro parts is paid attention. In this paper, we examined the development of the embossing roll with patterns of micron level and we tried to make the embossing roll mold by using the LIGA process. In this study, instead of producing embossing patterns directly on the roll surface, we fabricated a flexible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 2 publications
0
38
0
1
Order By: Relevance
“…Recent studies have reported that the imprinted microstructure is correlated to key process parameters such as embossing temperature, roller speed, and roller embossing pressure (Ishizawa et al 2008;Ng and Wang 2009;Yeo et al 2009Yeo et al , 2010. It was found that higher process temperature and process pressure are usually required.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent studies have reported that the imprinted microstructure is correlated to key process parameters such as embossing temperature, roller speed, and roller embossing pressure (Ishizawa et al 2008;Ng and Wang 2009;Yeo et al 2009Yeo et al , 2010. It was found that higher process temperature and process pressure are usually required.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the polydimethylsiloxane (PDMS) soft roller mold (Wu et al 2009) used in UV roller embossing is not suitable. A commonly used roller mold fabrication method involves electroplating the nickel microstructure onto a flexible metal film and wrapping it onto the cylinder roller to form a robust roller mold (Ishizawa et al 2008;Ng and Wang 2009;Yeo et al 2009Yeo et al , 2010. Other methods, such as spin coating liquid crystal polymer (LCP) (Shan et al 2010) or poly(urethane acrylate) (PUA) (Seo et al 2007) onto a flexible sheet, are also effective methods for hot roller embossing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we performed what the most suitable bump shape derived, manufacture by the UV-LIGA process and evaluation by the photocatalyst. In addition, in our laboratory, we perform injection molding and molding by the roller hot embossing (Ishizawa et al 2008), but this study uses the injection molding.…”
Section: Introductionmentioning
confidence: 99%
“…Both roller embossing and roll-to-roll embossing are cost-effective and productive approaches for high volume fabrication once the embossing moulds are generated, and they have been used in fabricating components for micro optical (Chang et al 2006), microfluidic devices (Velten et al 2008) as well as textile fibers (Schift et al 2006). There are three methods for mould configuration: (1) the template patterns are fabricated directly on a roller surface via chemical etching (Jiang et al 2008;Ishizawa et al 2008), plating or precision machining; (2) the patterns are formed on a thin film via etching or plating, the patterned thin film is overlapped atop plastic substrate and fed through the embossing rollers (Shan et al 2009); (3) the patterns are fabricated on a thin and flexible film to form an embossing mould, and the mould is wrapped around an embossing roller (Ahn and Guo 2008). Flexible moulds, which were frequently used in above (2) and (3), were fabricated via photolithograph and nickel plating on thin nickel foils.…”
Section: Introductionmentioning
confidence: 99%